Prevalence and reduction of Streptococcus mutans, Streptococcus sobrinus, and Streptococcus sanguinis in Vietnamese students following fluoride varnish application - Pham Thi, Ngoc Nga; Truong Thi, Bich Van (Academia Journal of Biology, 2025)
Dental caries is a multifactorial disease influenced by microbial composition, host-related factors, and environmental conditions. Streptococcus mutans and Streptococcus sobrinus are key contributors to caries progression, while Streptococcus sanguinis has a more complex role in caries development. This study aimed to determine the prevalence of S. mutans, S. sobrinus, and S. sanguinis in dental plaque among Vietnamese students and evaluate the antibacterial effects of fluoride varnish over a six-month period.A cross-sectional analytical study was conducted at Vo Truong Toan Primary School, Can Tho City, Vietnam. Dental plaque samples were collected from 77 children with active caries and analyzed using PCR. Fluoride varnish (Clinpro™ White Varnish) was applied at baseline and three months post-treatment. Bacterial presence was re-evaluated at three and six months. The initial prevalence of S. mutans, S. sobrinus, and S. sanguinis was 50.6%, 14.3%, and 1.3%, respectively. After three months, S. mutans prevalence significantly declined to 19.5%, while S. sobrinus remained stable at 13.0%, and S. sanguinis increased slightly to 3.9%. At six months, S. mutans further decreased to 11.7%, and S. sobrinus to 6.5%, while S. sanguinis was detected in 2.6% of cases. The proportion of bacteria-free samples increased from 23.4% before treatment to 77.9% after six months. The findings confirm the dominant role of S. mutans in dental caries and highlight the sustained antibacterial effects of fluoride varnish in reducing its prevalence. S. sobrinus was detected less frequently but remained a significant contributor to caries, while S. sanguinis showed variable presence. These results support the use of fluoride varnish as a preventive measure for caries management. Future studies should explore bacterial load quantification, metagenomic profiling, and the long-term impact of fluoride varnish on microbial communities.